Study of Physico-Chemical Changes of CdTe QDs after Their Exposure to Environmental Conditions - Hosnedlova, Bozena; Vsetickova, Michaela; Stankova, Martina; Uhlirova, Dagmar; Ruttkay-Nedecky, Branislav; Ofomaja, Augustine; Fernandez, Carlos; Kepinska, Marta; Baron, Mojmir; Ngoc, Bach Duong; Nguyen, Hoai Viet; Thu, Ha Pham Thi; et al. (Nanomaterials (Basel, Switzerland), 2020)
The irradiance of ultraviolet (UV) radiation is a physical parameter that significantly influences biological molecules by affecting their molecular structure. The influence of UV radiation on nanoparticles has not been investigated much. In this work, the ability of cadmium telluride quantum dots (CdTe QDs) to respond to natural UV radiation was examined. The average size of the yellow QDs was 4 nm, and the sizes of green, red and orange QDs were 2 nm. Quantum yield of green CdTe QDs-MSA (mercaptosuccinic acid)-A, yellow CdTe QDs-MSA-B, orange CdTe QDs-MSA-C and red CdTe QDs-MSA-D were 23.0%, 16.0%, 18.0% and 7.0%, respectively. Green, yellow, orange and red CdTe QDs were replaced every day and exposed to daily UV radiation for 12 h for seven consecutive days in summer with UV index signal integration ranging from 1894 to 2970. The rising dose of UV radiation led to the release of cadmium ions and the change in the size of individual QDs. The shifts were evident in absorption signals (shifts of the absorbance maxima of individual CdTe QDs-MSA were in the range of 6-79 nm), sulfhydryl (SH)-group signals (after UV exposure, the largest changes in the differential signal of the SH groups were observed in the orange, green, and yellow QDs, while in red QDs, there were almost no changes), fluorescence, and electrochemical signals. Yellow, orange and green QDs showed a stronger response to UV radiation than red ones.
Keywords: UV radiation; quantum dots; fluorometric detection; electrochemistry detection